2017
DOI: 10.4038/sljas.v22i1.7516
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the most suitable crustacean exoskeleton waste from fish processing industry to isolate chitosan

Abstract: Shell waste produced by the sea food industry is one of the most significant problems contributing for environmental and health hazards. The most frequent method employed for disposal of these waste is burning which is environmentally costly due to low burning capacity of shells. In such a scenario, conversion of shrimp shell waste to chitosan, a commercially valuable product with a myriad of uses, could serve as an effective mode of shell remediation. Chitosan was obtained from shellfish waste by deproteinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…The present study showed a higher chitosan yield (33.53%) over the previous studies from Penaues monodon shells (24.27%) by Sanuja et al (2017) and Metapenaeus stebbingi shells (17.5%) by Kucukgulmez et al (2011). However, Allwin et al 2015 have been reported a high yield compared to the present study for Litopenaeus vannamei which was 47%.…”
Section: Physicochemical Characteristics Of Extracted Chitosancontrasting
confidence: 67%
See 2 more Smart Citations
“…The present study showed a higher chitosan yield (33.53%) over the previous studies from Penaues monodon shells (24.27%) by Sanuja et al (2017) and Metapenaeus stebbingi shells (17.5%) by Kucukgulmez et al (2011). However, Allwin et al 2015 have been reported a high yield compared to the present study for Litopenaeus vannamei which was 47%.…”
Section: Physicochemical Characteristics Of Extracted Chitosancontrasting
confidence: 67%
“…Coupling of NH bending vibrations of NH2 group in chitosan with amide-II band may account for the broadband in the frequency of 1,553 cm -1 (Ghimire et al 2011). The degree of deacetylation was 80.43% and it was a comparatively high value with past studies which reported a degree of deacetylation of 40% by Sanuja et al (2017), 61% by Kumari et al (2015) and 74.82% by Mohanasrinivasan et al (2014).…”
Section: Ftir Analysissupporting
confidence: 54%
See 1 more Smart Citation
“…The FTIR method reported by Sanuja et al [10] was adopted in determining the degree of deacetylation. To a known weight of chitosan (dried at 60 o C) was added 200 mg potassium bromide tablet.…”
Section: Degree Of Deacetylation Estimation Using Infrared Spectroscopymentioning
confidence: 99%
“…After drying the chitosan extract, the dried chitosan was weighed and the chitosan content was calculated as follows: Yield (%)=(weight of chitosan, g)/(weight of beetle exoskeleton, g)×100 [22]. The ash content of chitosan was determined gravimetrically by combustion in an air atmosphere using a constant weight crucible at 550°C for 3 h.The degree of deacetylation (DD) of chitosan was determined by FTIR spectroscopy using the following equation: DD (%) = 100 -[100*(A 1655 /A 3450 )/1.33] .Where: A 3450 and A 1655 are the heights of the absorption bands of the hydroxyl and amide groups, respectively.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%